(untitled) (SAARC Journal of Agriculture, 2017)
A field experiment was carried out at Rahuri (Maharashtra) India in consecutive years of 2011 to 2012 to study the response of split and foliar application of nitrogen on leaf nitrogen concentration, SPAD index and photosynthesis in Bt cotton (Gossypium hirsutum L). Ten treatments comprising nitrogenmanagement practices (application of recommended dose of nitrogen in 3, 4, 5, 6 splits; foliar application of 20 g KNO3 litre-1 water, 20 g urea litre-1 water, combination of split application of nitrogen and foliar spray of 20 g KNO3 litre-1 water, 20 g urea litre-1 water and control) were tested on inceptisol. Results indicated that application of nitrogen in six splits (20% at sowing as basal and remaining in 5 equal splits at 30, 45, 60, 75 and 90 DAS) registered significantly higher leaf nitrogen content, SPAD index and rate of photosynthesis except 60 DAS where 4 nitrogen split showed higher leaf nitrogen content and SPAD index. Similarly the same treatment registered significantly higher plant height, dry matter accumulation, number of bolls plant-1 and lint yield. SAARC J. Agri., 14(2): 1-11 (2016)